INNOVATION OF A TEACHING AIDS FOR ENERGY TRANSFORMATION TO IMPROVE ELEMENTARY SCHOOL STUDENTS SCIENCE PROCESS SKILLS - Riko Rohim; Mega Wati; Antok Kurniawan (SOSIOEDUKASI, 2026)
This study aims to develop learning media in the form of an energy transformation teaching aid kit to improve the science process skills of fourth-grade elementary school students. The type of research applied is Research and Development (R&D) using the ADDIE development model. Data collection was carried out using expert validation questionnaires, as well as questionnaires for teachers and students, along with learning outcome tests. The research subjects included 6 fourth-grade students in a limited-scale trial, followed by 18 fourth-grade students from SDN 32/II Muara Bungo in a wider trial. The data were analyzed through tests of validity, practicality, and effectiveness using a Likert scale approach. The results of the analysis show that (1) The validity of the media obtained a score of 96% and the validity of the material obtained a score of 95%, both of which are categorized as highly valid. (2) Practicality was assessed with teacher scores of 94% and student scores of 93% in the limited trial, and teacher scores of 94% and student scores of 92% in the wider trial, all of which are categorized as highly practical. (3) Effectiveness showed a classical completeness of 100%, indicating it is highly effective. Based on these results, it can be concluded that the developed energy transformation teaching aid kit is highly valid, highly practical, and highly effective, making it suitable for improving the science process skills of elementary school students in Grade IV Science (IPAS) learning